2019
DOI: 10.3390/cancers11060881
|View full text |Cite
|
Sign up to set email alerts
|

(Pro)renin Receptor Expression Increases throughout the Colorectal Adenoma—Adenocarcinoma Sequence and It Is Associated with Worse Colorectal Cancer Prognosis

Abstract: (Pro)renin receptor (PRR) is a protein that takes part in several signaling pathways such as Renin Angiotensin System and Wnt signalling. Its biological role has recently been related to cancer progression and in this study, we investigated its relevance in colorectal cancer (CRC). To that end, we analysed the immunohistochemical expression of PRR in adenomatous polyps and CRCs from the same patients (n = 42), and in primary tumours and nodal and liver metastases from advanced CRC patients (n = 294). In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 63 publications
5
11
0
Order By: Relevance
“…These results agree with studies carried out in other solid tumours, showing the potential of PRR as a biomarker of worse prognosis [21]. Furthermore, we reported recently that PRR staining was not very different in the centre and front of colorectal cancers [27], a result that was repeated in RCCs. This finding suggests that the intrinsic heterogeneity of these tumours may not affect their analysis, which is favourable for the potential use of PRR as an immunohistochemical prognostic biomarker [27].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results agree with studies carried out in other solid tumours, showing the potential of PRR as a biomarker of worse prognosis [21]. Furthermore, we reported recently that PRR staining was not very different in the centre and front of colorectal cancers [27], a result that was repeated in RCCs. This finding suggests that the intrinsic heterogeneity of these tumours may not affect their analysis, which is favourable for the potential use of PRR as an immunohistochemical prognostic biomarker [27].…”
Section: Discussionsupporting
confidence: 92%
“…Our data show cytoplasmic granular staining of PRR in RCCs, which could be associated with these intracellular phenomena. PRR has also been described in benign tumours, such as adrenal [46,47] and colorectal adenomas [27]. In agreement with this, our results showed that PRR was expressed in RO and with the same intensity as in ChRCC, tumours that are histogenetically related [6].…”
Section: Discussionsupporting
confidence: 91%
“…We found that higher (P) RR expression levels are more commonly observed in patients with the following characteristics: male sex, early age at onset, poorly differentiated lesions, advanced cancer stage, distant metastasis, rapid progression, lower 5-year survival rate and shorter recurrence-free survival time (Table 1). Recently, Maider et al [44] reported their latest data which are highly consistent with our previous findings. In their study, (P) RR protein levels were detected in tissues of adenomatous polyps and cancers from the same CRC patients (n = 42), as well as in tissues of primary tumors and nodal and liver metastases from advanced CRC patients (n = 294) [44].…”
Section: Crcsupporting
confidence: 91%
“…In their study, (P) RR protein levels were detected in tissues of adenomatous polyps and cancers from the same CRC patients (n = 42), as well as in tissues of primary tumors and nodal and liver metastases from advanced CRC patients (n = 294) [44]. The results showed that (P) RR expression increases throughout the colorectal adenoma-adenocarcinoma process, moreover, (P) RR protein in both primary tumor and distant metastases is associated with worse prognosis including 5-and 10-year survival of CRC patients [44].…”
Section: Crcmentioning
confidence: 99%
See 1 more Smart Citation